Diversity of Insect Pests in Plants of Coffee (Coffea arabica L.) in Sigumpar, Humbang Hasundutan, North Sumatera - Nursal bio (Talenta Publisher, 2021)
Both methods were carried out in 5 locations based on the age of coffee, 3, 5, 10, 15, and 20 years. The area of the Searching and Direct Observation and Hand Picking method is 20x20 meters which was carried out diagonally. Data collected included the number of species and individuals, density (K), relative density (KR),attendance frequency (FK), diversity index (H '), equitability index (E) and its similarity index (IS). The results of the observation showed that 4 pest orders, 8 families, 10 species and 225 individuals were obtained. During the day 9 species of insects were found with 4 orders, 7 families, and 198 individuals and at night there were 4 types of insects with 2 orders, 3 families and 31individuals. Hypothenemus hampeii is the species with the highest K, KR and FK values of all locations with each value of 0.045 ind / m2, 41.86% and 100%. The highest Diversity Index (H ') value is found at location 5 (1,841) and the lowest value at location 1 (1,178). The highest Equitability value (E) is found in location 1 (0.849) and the lowest value at location 5 (0.799). The highest Similarity Index (IS) is found in locations 4 and 5 with a value of 94.73% and the lowest at locations 1 and 5 with a value of 57.14%.